Edgar Schein's model of organizational culture levels as a hologram - Kiril Dimitrov (Economic Studies (Ikonomicheski Izsledvania), 2013)
The current study dwells upon Edgar Schein's original framework for exploring organizational culture by classifying its elements to three levels. Important directions of model's elaboration are identified and analyzed. The last have been undertaken by different researchers in the last three decades, based on individual's necessities, involvement and experience with the application in practice of this model. Viewing Schein's model as a hologram is recommended as a way to dissolve subjectively identified by different authors issues or ambiguities in this framework. Thus, a contemporary, useful and richer “snapshot” of this model is proposed for use in the organizations during these turbulent times when cultural intelligence capabilities come of greater importance for their successful market performance.
Keywords: M14; L20; 650; organizational culture; firm culture; levels of culture; Edgar Schein; studying of a culture